Adaptive griffiths scale − modern experience in assessing the psychomotor development of preschool children - Bedrii, Nataliia (Journal of Education, Health and Sport, 2021)
Premature newborns build a specific category of children due to their innate morpho-functional immaturity and specific pathological conditions that determine significant survival, morbidity and postnatal care results as compared to children of other weight categories. In the long-term adverse effects of preterm birth, the incidence of neuropathy remains high and requires further improvements in diagnostic methods and timely corrections for a better developmental prognosis. Although over the past three decades, numerous tools have been invented to predict long-term adverse effects of preterm neonates as well as methods for determining degree of disorders, neither these tools nor their weak and strong points have undergone a comprehensive overview. Aim of the research was to improve long-term preterm birth outcomes by using the adaptive Griffiths scale for preschoolers. The psychomotor development of 105 preschoolers was evaluated. Assessment of indicators of psychomotor development was carried out by the adaptive Griffiths scale and the conventional method. In the course of the study, this category of children was under doctors’ from Neonates Post-discharge Follow-ups Department with systematic evaluation of their health condition. Dynamic examination was performed during the first year of life once per 3 months, from the 2nd to the 6th year of life – corresponding to an individual rehabilitation plan. Patients (n=105) were divided into 3 groups depending on the severity of the disabling pathology. The analysis of indicators of psychomotor development (by traditional methods) of prematurely born preschoolers, divided into 3 groups in accordance with severity degree of disabling pathology: Group A children with severe long-term consequences that led to disability – 54 (51.4%) Group B. Children with long – term consequences who are subject to correction - 24 (22.8%) Group C. Children with long-term consequences not significantly affecting their health condition -27 (25.7%). The conducted survey suggests, that above 70% of the children had various patterns of delayed psychomotor development. The assessment of psychomotor development showed that the cause structure of delayed psychomotor development of preschoolers has the same trend according to different examination methods, but the assessment by the adaptive Griffiths scale shows more accurate values for each patient, enables quick detection of long-term adverse consequences of premature birth, recommendations for parents for neonates’ rehabilitation and habilitation, as well as examination in dynamics. In the flow of the research, the adaptive Griffiths scale of psychomotor development proved to be a valid diagnostic tool for determining indicators of preschoolers’ psychomotor development, estimating their intellectual coefficient and forming individual patient’s profile.